Food for thought: analysing the internal and external school food environment. Issue 2 (2nd February 2015) - Callaghan, Mary; Molcho, Michal; Nic Gabhainn, Saoirse; Kelly, Colette
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Availability and access to food is a determinant of obesity. The purpose of this paper is to examine food availability within and outside of post-primary schools in Ireland. Design/methodology/approach – Data on the internal school food environment were collected from 63 post-primary schools using questionnaires. The external school food environment for these 63 schools was assessed by mapping food businesses within 1 km of schools, using a Geographic Information System (GIS). Food businesses were categorised based on type of food sold. Findings – A total of 68.3 per cent of schools had a canteen, 52.5 per cent had a small food shop and 37.1 per cent had a vending machine. A total of 32.7 per cent of schools reported selling chips (French fries) in their canteen while 44.2 per cent of schools reported selling energy-dense nutrient-poor foods in their school shop. Of the schools surveyed, there was an average of 3.89 coffee shops and sandwich bars, 3.65 full service restaurants, 2.60 Asian and other "ethnic" restaurants, 4.03 fast food restaurants, 1.95 supermarkets, 6.71 local shops and 0.73 fruit and vegetable retailers within a 1 km radius of the post-primary schools. Findings are presented by geography (urban/rural), disadvantage (Delivering Equality of Opportunity in School (DEIS)/non DEIS), gender (girls/boys/mixed) and food policy in place at the school (yes/no). Practical implications – These data will facilitate schools working on the framework for Health Promoting Schools in Ireland. Social implications – This work can contribute to current discussions on restricting accessibility to certain foods and food premises for school children. Originality/value – The study explores the internal and external school food environment. GIS have been used to link the external food environment to specific schools thus allowing a comprehensive analysis of the schools' food environment. To the authors knowledge, this is the first time that both environments are explored simultaneously.